Temperament, character traits and alexithymia in patients with obsessive compulsive disorder - Mehmet Üstündağ; Pınar Şen Gökçeimam (Family Practice and Palliative Care, 2020)
Introduction: Alexithymia levels have generally been found high in patients with obsessive compulsive disorder (OCD). It is thought that there is a correlation between alexithymia and the severity of OCD symptoms. One of the factors influencing alexithymia is temperament-character traits. In this study, it was aimed to investigate the temperament-character traits in OCD patients and the correlation of these traits with alexithymia. Methods: This study included 43 OCD patients who applied to Atatürk University Psychiatry Outpatient Clinic and 33 healthy individuals as the control group. Structured Clinical Interview for DSM-IV Axis I Disorders (SCID-IV), Sociodemographic and clinical data form, and Temperament and Character Inventory (TCI), Toronto Alexithymia Scale (TAS-20) were applied to participants whereas Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) was additionally applied to the patient group.Results: No difference was detected between both groups in terms of age and gender. In the OCD group, harm avoidance (HA) and self-transcendence (ST) scores were found high, and self-directedness (SD), cooperativeness (C) and novelty seeking (NS) were found low when compared to the control group. In the OCD group, difficulty in expressing feelings (TAS-B), extroverted thinking (TAS-C) and TAS-20 scores were found to be higher than the control group. In the alexithymic OCD group, the mean disorderliness and persistence(P) scores were found to be lower compared to the non-alexithymic group. A positive correlation was discovered between Y-BOCS scores and TAS-C scores in OCD patients.Conclusion: Alexithymia is observed at a high rate in OCD. The extroverted thinking sub-dimension of alexithymia is correlated with the severity of OCD symptoms. Some temperament-personality traits differ in alexithymic-OCD patients compared to those who are not alexithymic. The evaluation of alexithymia and the factors influencing alexithymia has the potential to offer a new approach to understand the etiology and treatment of OCD.